“How often can you ask your reader to leave?” Text and Reader in Lars Skinnebach: Din misbruger (You/r addict) - Ølholm, Marianne (Nordlit, 2007)
A characteristic feature of Avant-garde art is the radical approach to established artistic forms. One way of describing tradition and norms of artistic expression is through genre: Literary genre represents a set of conventions which are transcended by the experimental text. The poetic genre can be defined through the expectations of the reader, and this approach seems particularly relevant in the case of Lars Skinnebach's Din misbruger (You/r addict) (2006) as this work actively addresses the role of the reader, his or her expectations of the text, and the status of the work as an object of interpretation. This paper investigates the conditions of the construction of poetic voice in the Din misbruger (You/r addict) and how it challenges the role of the reader as well as the status of the text as a literary product.